CONTINUING EDUCATION AT THE INTERFACE WITH DISTANCE EDUCATION - Barbosa Cruz, Isabela; Neco Rocha, Anderson; Stefany Cardoso Nascimento, Mariana; Rocha de Oliveira, Byan; Faria de Magalhães, Andreza; Anelita Pereira Souza, Lunny; Gonçalves Ribeiro, Natália; Moura Figueiredo, Nathália; Carlos Pereira de Jesus, Ely; Antunes Dutra, Carlos; Caldas Silva, Charles; Alves Moraes Nogueira, Edila; et al. (Health and Society, 2024)
This study aimed to list the main positive points of the use of Distance Education (Distance Education) in Continuing Health Education according to the national literature. This is an integrative review carried out during the first half of 2016, and data collection was performed from the following databases: Scientific Electronic Library Online (Scielo) and journals in the field of education. The results obtained were tabulated and the main results of each study included were scored. In this sense, it is possible to consider that THE has been gaining space in the health area because it has many advantages. The consolidation of PHE, the EaD has been gaining great strength in recent years, being widely used in the health area due to meeting the needs of these areas. In view of this growing use, there are numerous questions about its use, and it is necessary to analyze its pros and cons.